From noticing to reflection: A qualitative exploration of rapid cycle deliberate practice effects on electrocardiographic monitoring judgment in critical cardiac care nurses - Jun Xie; Wenyu Yue; Xiaoyan Wu; Lili Wu (PLoS ONE, 2026)
Background Electrocardiographic interpretation competency among critical cardiac care nurses remains inadequate despite technological advances, creating patient safety concerns and alarm fatigue. Traditional nursing education utilizing didactic knowledge transmission has proven insufficient for developing time-critical electrocardiographic interpretation skills. Rapid cycle deliberate practice emerges as an innovative methodology integrating deliberate practice principles, immediate feedback, and psychologically safe environments through pause-coach-resume mechanisms. Methods Semi-structured interviews utilized Tanner’s clinical judgment model as the questioning framework, supplemented by field observations. Interviews explored experiences around the noticing-interpreting-responding-reflecting continuum, with analysis conducted using NVivo software following van Manen’s methodology. Results Four interconnected themes emerged: shifting perceptual focus from fragmented data perception toward holistic pattern recognition; shifting cognitive models from mechanical matching toward integrating intuition and evidence; evolving response patterns from hesitant reactivity toward confident proactivity; and redefined professional role encompassing new professional identity, ethical responsibility, and continuous learning commitment. Conclusions Analysis through Tanner’s clinical judgment framework suggested perceived multidimensional shifts within critical cardiac care nurses’ clinical judgment processes, as reflected in participants’ descriptions of changes transcending technical skill acquisition to encompass reconceptualizations of clinical reasoning, professional identity, and ethical responsibility. Notably, the psychologically safe environment created through the pause-coach-resume mechanism appeared central to enabling these perceived shifts. These findings indicate that effective competency development requires educational approaches addressing cognitive, behavioral, and identity dimensions simultaneously, with implications for institutional integration of rapid cycle deliberate practice into staff development and future longitudinal investigation of its effectiveness.